(untitled) (International conference on multidisciplinary science, 2026)
Endometrial cancer in patients over 50 years old, compared with the group of 60-75 years old, is characterized by a predominance of high-grade carcinomas (27.2% versus 12%, p < 0.001) due to the prevalence of non-endometrioid tumor histotype (16.98% versus 4.7%, p = 0.005). Extensive forms of the disease (FIGO stages III-IV) among women aged ≥ 70 years were observed in 17.6% of cases versus 6.7% in the comparison group (p = 0.003). The studied age groups were comparable in the extent of surgical treatment (p = 0.637) and adjuvant therapy performed in the postoperative period (p = 0.749).